PS-P15-6: PERIPHERAL OSTEOPONTIN MIGHT BE A POTENTIAL BIO-MARKER FOR PREDICTING ARTERIAL STIFFNESS IN ELDERLY CHINESE. (January 2023) - Fu, Guoxiang; Pan, Fengfeng; Xu, Chanchan
Abstract : Objective: Compare the efficiency of pulse wave velocity (PWV) and ankle-brachial Index (ABI) in diabetes patients and healthy participants. Investigate novel bio-markers for aging related arterial stiffness. Design and method: PWV, ABI, vascular cell adhesion molecule (VCAM), osteopontin (OPN) and glutathione peroxidase (GPX) were evaluated in elderly Chinese from March to June in 2019. Results: 86 participants were included in the study. There were 69 male participants (80.2%), the mean age is 87.2 ± 0.5 years, the mean BMI is 23.3 ± 0.5. Of the 86 participants, 34 were diagnosed with diabetes mellitus. Compared with non- diabetes mellitus participants, ABI levels declined in left limbs of diabetes mellitus (DM) patients (0.94 ± 0.04 vs 1.02 ± 0.03, P < 0.05, separately). After adjusted by age, SBP, DBP, BMI, FPG, Cholesterol and HCT, serum OPN level was negatively correlated to both L- ABI and R- ABI (r = - 0.317, P = 0.028; r = - 0.362, P = 0.014, separately). Conclusions: Differential use of PWV and ABI should be considered in elderly with diabetes. Serum levels of OPN might be an independent bio-marker for predicting arterial stiffness in elderly Chinese.